Deformation Behavior of Optical Ceramic Nanomultilayers: The Role of Aperiodicity - White, Danielle E.; Cheng, Wenjuan; Jagadish, Koushik; Rossi, Edoardo; Shao, Yu‐Tsun; Hodge, Andrea M. (Advanced engineering materials, 2025)
Aperiodicity in ceramic nanomultilayers (NMs) has been shown to improve coating functionality, namely, for optimized optical behavior, while the effects of aperiodic layer thicknesses on mechanical deformation remain poorly understood. In this article, the relationships between individual layer thicknesses, optical transmittance, and mechanical behavior are investigated for AlN/Al2O3, YSZ/Al2O3, and AlN/YSZ nanomultilayered coatings. These NMs are synthesized with aperiodic layer configurations from individual constituents selected for their optical constants, elastic modulus, and hardness values; the layer designs of select samples are optimized to achieve a transmittance exceeding 90% across the ultraviolet, visible, and near‐infrared spectral range. The effect of aperiodicity on the mechanical properties and deformation is explored at various length scales via nanoindentation, micropillar splitting, and Vickers microindentation. However, competing factors, such as interface type and local microstructure, also play critical roles. It is observed that layer composition strongly influences fracture toughness, as samples with amorphous Al2O3 layers and crystalline/amorphous interfaces exhibit superior mechanical performance and the highest fracture toughness values. Yet, distinct failure modes, including delamination and intergranular fracture, across the different nanomultilayered architectures highlight the relation of optical and mechanical properties to local volume fractions within aperiodic layer stacks and interface characteristics in the coating design. Ceramic nanomultilayers demonstrate optical and mechanical behavior tunability through aperiodicity. Within the studied systems, optically optimized coatings exhibit an average ultraviolet, visible, and near‐infrared spectral transmittance above 90%. Residual stress, local volume fractions within layer stacks, and layer composition are shown to influence mechanical deformation, where crystalline/amorphous interfaces and/or Al2O3 are linked to the highest fracture toughness.